Niektóre polityczne skutki reelekcji włodarza gminy – analiza na przykładzie miejscowości z województwa kujawsko-pomorskiego, świętokrzyskiego i opolskiego - Kubisz-Muła, Łukasz (Polityka i Społeczeństwo, 2020)
The supporters of the idea of introducing a term limit for Vogts and mayors argue that long-lasting incumbency leads, among other things, to atrophy of political involvement at the local level. The aim of the article is to validate the above-mentioned belief through checking how the duration of tenure of Vogts and mayors affects the voter turn-out and the number of candidates in the local elections. The study draws on the data from National Electoral Commission regarding the results of and candidates in the local elections (2002, 2006, 2010 and 2014) in 317 Polish electoral districts. The statistical analysis reveals that time of incumbency can correlate negatively with political engagement in some aspects, although these relationships are not very strong.